Development of Engineering Vocational Choice Systems in Higher Education - elsa sabrina; Muhammad Anwar; Hansi Effendi; Resmi Darni (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The high unemployment rate is a challenge for the world of education because not all graduates succeed in entering the world of work. Higher education is one of the largest contributors to unemployment in Indonesia. Likewise with the objectives of vocational education which are expected to be able to immediately work and create jobs. The problem is that not all majors are according to personality type. Therefore, researchers will develop a system aimed at recommending majors in higher education based on personality types. The method used is the Research and Development (R&D) method using the Four D (4 D) model a. Defining stage (Define); b) Design Stage (Design); c) Development Stage (Develop); d) Stage of Spread (Disseminate). This research was only carried out to the extent of development and resulted in a valid system to be implemented based on the validator's assessment. The data collection instrument consisted of product and linguistic expert validation sheets. This study shows that the validation results have an average percentage of 92.5% with a valid category. Based on the results of the research and discussion, it can be concluded that the system is valid to be used as a reference in selecting majors